Chinese Dragon’s Blood EtOAc Extract Inhibits Liver Cancer Growth Through Downregulation of Smad3 - Chen, Xiaonan; Zhao, Yanan; Yang, Ailin; Tian, Yingying; Pang, Daoran; Sun, Jing; Tang, Leimengyuan; Huang, Huiming; Wang, Ying; Zhao, Yunfang; Tu, Pengfei; Hu, Zhongdong; et al. (Frontiers in Pharmacology, 2020)
Hepatocellular carcinoma (HCC) is one of the most prevalent malignancies, which ranks the third leading cause of cancer-related death worldwide. The screening of anti-HCC drug with high efficiency and low toxicity from traditional Chinese medicine (TCM) has attracted more and more attention. As a TCM, Chinese dragon’s blood has been used for the treatment of cardiovascular illness, gynecological illness, skin disorder, otorhinolaryngological illness, and diabetes mellitus complications for many years. However, the anti-tumor effect and underlying mechanisms of Chinese dragon’s blood remain ill-defined. Herein we have revealed that Chinese dragon’s blood EtOAc extract (CDBEE) obviously suppressed the growth of human hepatoma HepG2 and SK-HEP-1 cells. Moreover, CDBEE inhibited the migration and invasion of HepG2 and SK-HEP-1 cells. Additionally, CDBEE displayed good in vitro anti-angiogenic activity. Importantly, CDBEE treatment significantly blunted the oncogenic capability of HepG2 cells in nude mice. Mechanistically, CDBEE inhibited Smad3 expression in human hepatoma cells and tumor tissues from nude mice. Using RNA interference, we demonstrated that CDBEE exerted anti-hepatoma activity partially through down-regulation of Smad3, one of major members in TGF-β/Smad signaling pathway. Therefore, CDBEE may be a promising candidate drug for HCC treatment, especially for liver cancer with aberrant TGF-β/Smad signaling pathway.